2015
DOI: 10.1111/jdv.12900
|View full text |Cite
|
Sign up to set email alerts
|

Personal vs. intrinsic melanoma risk awareness: results of the EDIFICE Melanoma survey

Abstract: Background The efficiency of skin cancer prevention programmes is strongly correlated with the information dis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, similarly to previous studies [22,28], our results demonstrated that caregivers possessed relatively accurate knowledge regarding the biological effects of UV light. However, this premise does not necessarily translate into appropriate sun-safe behavior [37]. The knowledge level regarding different skin types improved following our presentation, but the difference was not significant.…”
Section: Discussionmentioning
confidence: 80%
“…However, similarly to previous studies [22,28], our results demonstrated that caregivers possessed relatively accurate knowledge regarding the biological effects of UV light. However, this premise does not necessarily translate into appropriate sun-safe behavior [37]. The knowledge level regarding different skin types improved following our presentation, but the difference was not significant.…”
Section: Discussionmentioning
confidence: 80%